Synthesis and characterization of sustainable polyurethane foams based on polyhydroxyls with different terminal groups. (1st August 2018) - Stanzione, M.; Russo, V.; Oliviero, M.; Verdolotti, L.; Sorrentino, A.; Di Serio, M.; Tesser, R.; Iannace, S.; Lavorgna, M.
Abstract: Several bio -based polyhydroxyls are successfully synthesized by using succinic acid, obtained via Arundo donax fermentation and characterized by 1 H NMR, GPC, and FT-IR analyses. Furthermore, the bio -based polyhydroxyls, consisting of a wide spectrum of compounds in terms of chemical structure and molecular weight, are used as substitute of conventional polyol in the formulations of Polyurethane and random Urethane-Amide Copolymer bio -based foams. The influence of both amount and typology of bio -based polyhydroxyls on bio -based foam properties is investigated through kinetic analysis, thermo-mechanical characterization, and morphological analysis. The results highlight that the replacement of conventional polyol with the bio -based polyester polyhydroxyls affects the foaming process and consequently the final properties of the free-foamed materials. In particular, the compressive modulus increases by about 140% for a bio-based polyhydroxyl content of 50 wt% together with an increase in foam density. A further increase of these adducts results in a decrease of the glass transition temperature and the mechanical performances. However, the experimental results demonstrate the potentiality of these bio-based foams as commodity in several applications. Graphical abstract: Image 1 Highlights: Bio-based polyhydroxyls were successfully synthesized by using bio-based feedstock. Polyurethane and urethane-amide foams were produced from bio-based polyhydroxyls. The foams exhibit chemico-physical performances comparable to conventional foams.